A cross-sectional study on smartphone use and mindfulness among undergraduate medical students of a medical college in Kolkata - Sanjay Kumar Saha; Soma Chakrabarti; Ankita Mishra; Aparajita Mondal; Moumita Mandal; Mausumi Basu (Asian Journal of Medical Sciences, 2024)
Background: Nowadays, increasing use of smart phone has led to smart phone addiction. Even medical students are inadvertently using these devices for non-academic purposes. Excessive smart phone use can impact mindfulness, which, in turn, can hamper patient care. Aims and Objectives: The objective of this study was to assess the smart phone usage and mindfulness among Undergraduate Medical Students of a Medical College, Kolkata. Materials and Methods: An observational study and cross-sectional in design was conducted from October 01, 2022, to December 12, 2022, among 423 undergraduate medical students of a medical college in Kolkata selected by simple random sampling technique using a pre-designed pre-tested structured questionnaire (containing mindful attention awareness scale). Besides, assessment of Digital Wellbeing and Parental Control application was done. Data were analyzed using Microsoft Office Excel 2019 and SPSSv25. Descriptive and inferential statistics were used to represent the data. Results: Over 80% participants were using their smart phones excessively and 52.5% students were unmindful. YouTube (26.9%) was the maximally used application. The participants spent 360 min/day on smart phone on an average. Being a male had a higher odd of excessive smart phone usage. Hostel residents were more mindful than others. Duration of smart phone use had a positive relation with mindfulness (Spearman’s rho 0.108, P=0.026). Conclusion: The participants spent a major portion of the day in front of smart phone screens. Smartphone use had a positive impact on mindfulness. By setting boundaries, that is, limiting daily usage in websites and apps, smart phone use can be reduced.